Assessment of acute toxicity, behaviours and water parameter correlations in nile tilapia (Oreochromis niloticus) exposed to iron salts - Orden, Carina B. (Penerbit Universiti Kebangsaan Malaysia, 2025)
The study determined the acute toxicity levels and behaviors of Nile tilapia after 96 h exposure to iron salts. It determined the significant correlations (Pearson’s r) between the water parameters, behaviors, and toxicity levels at varied time intervals and concentrations. This study adopted an experimental design framework, randomized triplicate sampling, and OECD Test Guideline No. 203. The acute toxicity test was done in a static method, behavioral clinical signs and opercular beats. Water parameters of pH, temperature, dissolved oxygen (DO), and total organic carbon (TOC) were measured using standard procedures of the OECD Test Guideline No. 203 and Association of Official Analytical Chemists (AOAC). The findings showed the lethal concentration (LC50) and lethal time (LT50) of total ferrous and ferric sulfate were 135.6 mg/L, 9.9 mg/L, and 340 h and 216 h, respectively, through probit analysis. Behaviors were abnormal bottom distribution, hypoventilation, abnormal pigmentation, and bioaccumulation of ferric ions. Opercular beats (OB) decreased as the concentration increased after 96-h exposure. Strong correlations (α = 0.05) were observed between concentration and the water parameters OB and pH in the ferric sulfate solutions, between pH, hardness, TOC, OB, and DO in ferrous sulfate solutions. The findings showed that ferric sulfate poses a greater risk than ferrous sulfate to test animals, implying its use and discharge should be limited in aquatic environments. The water parameters that significantly affected the toxicity levels must be monitored and regulated to mitigate potential adverse effects on aquatic ecosystems.